氢氟酸质量分数对二硅酸锂玻璃陶瓷表面形貌及树脂粘接的影响 (Hua Xi Kou Qiang Yi Xue Za Zhi, 2017)
OBJECTIVE: This study aimed at determining the influence of hydrofluoric acid (HF) in varied concentrations on the surface morphology of lithium disilicate glass ceramics and bond durability between resin composites and post-treated lithium disilicate glass ceramics. METHODS: After being sintered, ground, and washed, 72 as-prepared specimens of lithium disilicate glass ceramics with dimensions of 11 mm×13 mm×2 mm were randomly divided into three groups. Each group was treated with acid solution [32% phosphoric acid (PA) or 4% or 9.5% HF] for 20 s. Then, four acidified specimens from each group were randomly selected. One of the specimens was used to observe the surface morphology using scanning electron microscopy, and the others were used to observe the surface roughness using a surface roughness meter (including Ra, Rz, and Rmax). After treatment with different acid solutions in each group, 20 samples were further treated with silane coupling agent/resin adhesive/resin cement (Monobond S/Multilink Primer A&B/Multilink N), followed by bonding to a composite resin column (Filtek™ Z350) with a diameter of 3 mm. A total of 20 specimens in each group were randomly divided into two subgroups, which were used for measuring the microshear bond strength, with one of them subjected to cool-thermal cycle for 20 000 times. RESULTS: The surface roughness (Ra, Rz, and Rmax) of lithium disilicate glass ceramics treated with 4% or 9.5% HF was significantly higher than that of the ceramic treated with PA (P<0.05). The lithium disilicate glass ceramics treated with 9.5% HF also demonstrated better surface roughness (Rz and Rmax) than that of the ceramics treated with 4% HF. Cool-thermal cycle treatment reduced the bond strength of lithium disilicate glass ceramics in all groups (P<0.05). After cool-thermal cycle, the lithium disilicate glass ceramics treated with HF had higher bond strength than that of the ceramics treated with PA. The lithium disilicate glass ceramics treated with 4% HF had higher bond strength than that of the ceramics treated with 9.5% HF (P<0.05). During cool-thermal cycle, the lithium disilicate glass ceramics treated with 4% HF demonstrated higher reduction in bond strength than that of the samples treated with 9.5% HF (P<0.05). CONCLUSION: The concentration of HF significantly affected the surface morphology of lithium disilicate glass ceramics and the bond durability between resin composites and post-treated lithium disilicate glass ceramics. The bond strength between resin composites and post-treated lithium disilicate glass ceramic was more efficiently maintained by treatment with 9.5% HF.